The day we started HPV triage. Issue 9 (30th March 2016) - Deen, Suha; Vreynhoef, Sue; Gandhi, Nirav; Juliana, Anita; Nunns, David; O'Neill, David
Abstract : Aims: Following the introduction of the triage test in cervical screening, which was designed to identify a subgroup who were at risk of underlying high-grade cervical intraepithelial neoplasia (CIN), there has been a significant change in the number and profile of cervical biopsies. In this study, analysis of the progressive change in diagnostic categories has been performed to identify the impact of the triage test on the service. Methods: Cases referred for colposcopy, with corresponding subsequent tissue diagnoses, were identified by electronic search of the histopathology accession database using suitable coding terms for the period between October and April of four consecutive years. A likelihood ratio test was devised to assess the significance of the observed progressive increase in total numbers of cervical biopsies. Results: As anticipated from the pilot studies, implementation of the new guidelines led to a significant increase in the number of women referred for colposcopy. However, the annual increase was greater than expected. During this period, there was a change in the profile of histological diagnoses, characterised by: conspicuous rise in the number of cervical biopsies reported as 'human papillomavirus change only' or 'CIN1' (21–29% and 12–21%, of the total cervical biopsies, respectively); fall in mean CIN scores. Conclusions: The change in guidelines has led to an increase in patients referred for colposcopy; in turn this has led to an increase in number of specimens (particularly those with lower grades of dysplasia) submitted for histological assessment. This change of workload profile has implications for resourcing services for colposcopy and histopathology.